Sistematização do projeto de reatores eletrônicos para alimentação de lâmpadas de vapor de sódio em alta pressão para iluminação pública - Costa, Rafael Eduardo da (2009)
This thesis presents an electronic ballast prototype to supply high-pressure sodium lamps used in public lighting. The goal is to develop a commercial approach able to replace the still commonly used electromagnetic ballasts, performing improvements in the public lighting system. Along this thesis, the state of art in lighting area is presented, especially in public lighting. Following, a bibliographic review about electronic ballasts to supply highpressure sodium lamps is done. Special attention is given to the low frequency square waveform supplying method, which is used in this thesis. Also, the features desired in electronic ballasts so they can operate the lamp reliably and according to the standards are discussed. From this review, the proposed topology is defined and its design is presented. A discrete control method is developed to guarantee the safe operation of the ballast during all lamp stages. A microcontroller is used to perform the control routines. Finally, experimental results are obtained, validating the proposed work.